2022
DOI: 10.3390/nu14245296
|View full text |Cite
|
Sign up to set email alerts
|

Novel Horizons in Postbiotics: Lactobacillaceae Extracellular Vesicles and Their Applications in Health and Disease

Abstract: Lactobacillus probiotics contained in dietary supplements or functional foods are well-known for their beneficial properties exerted on host health and diverse pathological situations. Their capacity to improve inflammatory bowel disease (IBD) and regulate the immune system is especially remarkable. Although bacteria–host interactions have been thought to occur directly, the key role that extracellular vesicles (EVs) derived from probiotics play on this point is being unveiled. EVs are lipid bilayer-enclosed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Studies suggest that microvesicles derived from specific probiotic bacteria, such as Lactobacillus, may have immunomodulatory effects and influence processes related to cancer prevention and therapy. Some of the potential mechanisms under investigation include immunomodulation, anti-inflammatory effects, delivery of bioactive molecules, and communication with host cells [44][45][46] . One novel approach to treating and preventing gastrointestinal cancers is the utilization of human microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that microvesicles derived from specific probiotic bacteria, such as Lactobacillus, may have immunomodulatory effects and influence processes related to cancer prevention and therapy. Some of the potential mechanisms under investigation include immunomodulation, anti-inflammatory effects, delivery of bioactive molecules, and communication with host cells [44][45][46] . One novel approach to treating and preventing gastrointestinal cancers is the utilization of human microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, compared to the HFD group, we observed the limited effect on the ratio of F/B in the EGCG-treated groups, especially at low dose, which might be attributed to the high enrichment of the Lactobacillaceae family belonging to Firmicutes in the low-dose EGCG group by LEfse analysis. It has been reported that Lactobacillaceae protects healthy people against pathogenic infections, and supplementation of plant polyphenols, including catechins, leads to no significant change in the ratio of F/B when compared to the animals fed HFD . Moreover, previous studies have indicated that the increased levels of Proteobacteria and Spirochaetae as two phyla of Gram-negative bacteria, including their members, are closely associated with intestinal homeostasis, intestinal inflammation, and endotoxin production. , In a recent study, EGCG intervention significantly reversed the HFD-induced profound increases in the relative abundances of Proteobacteria and Spirochaetae, including Desulfovibrionaceae family and Spirochaetaceae family, as the dominant strain, which might contribute to the alleviation of intestinal inflammation and LPS production.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, another study showed that probiotic-derived EVs have a protective effect on Caco-2/HT29-MTX co-cultures exposed to enterotoxigenic E. coli , confirming the role of this bacterial structure in the maintenance of intestinal barrier integrity [ 141 ]. Considering their application in perspective, some authors also suggest that the administration of probiotic EVs alone could be a safer alternative than delivering live probiotics, especially in immunocompromised patients [ 146 , 147 , 148 ]. Moreover, in relation to some probiotic strains, the use of EVs alone could also represent an advantage in terms of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Although in those papers only eukaryotic cells-based vesicles were considered, we cannot ignore the fact that they show comparable structure and properties to bacterial ones, which lead us to believe that a similar application of probiotics-derived EVs is reasonable. In a recent work, González-Lozano et al [ 148 ] reported several examples of EVs’ applications in neurological disorders, focusing on their ability to transport active bacterial-produced compounds through different body districts. In addition, it is worth highlighting that the possibility to engineer EVs to improve their properties also exists.…”
Section: Discussionmentioning
confidence: 99%